Consejeria que reciben las adolescentes de la enfermera sobre planificación familiar por evento obstetríco - Resendiz Flores, Catalina (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
To analyze the Council that the teenagers receive on Familiar(Family) Planning Obstetric Pos Evento in the services of Tococirugía and Gíneco Obstetricia on the part of the Nurse. Methodology: The design of study was Quantitative, Descriptive and Transverse, the population was constituted by 100 teenagers who came to the service of tococirugía and gineco obstetrics of Coyuca's General Hospital of Catalan, Warrior. With a Sample of 30 teenagers selected by means of the method probabilístico Random Simple Sampling. I apply questionnaire to him (you, them) with categories of response dicotómicas and of multiple option to analyze the information I use the program SPSS Version 15 using Pearson's correlation to know the degree of association of the variables and Chicuadrada to prove(try) the significancia of the different proportions. Results: 50 % of the teenagers ranges between the age from 18 to 19 years. With a school level of preparatory 43.3 % the marital status finding an average between (among) spinsters and married. Correlation found the age of the teenager with the school level with one (r =.511, P =.004). Also one found correlation with the contraceptive methods with the religion with one (r=497, P=005) between (among) the contraceptive method chosen during the stay and the Council that has with the nurse is sufficient one found a strong correlation (r =.697 P =.000) in relation to the variables knowledge that there have the teenagers of the contraceptive methods and the nurse realizes physical examination one found a strong correlation (r =.613, P =.000). Discussion: in agreement to the opposing find the chosen methods have to see with the Council that the nurse offers these results coincide with those of Bernal, where the Council if it(he, she) influences 90 %. Conclusion: The Council that the nurse provides is influential in the decision of the contraceptive method.

Analizar la Consejería que reciben las adolescentes sobre Planificación Familiar Pos Evento Obstétrico en los servicios de Toco cirugía y Gineceo Obstetricia por parte de la Enfermera. Metodología: El diseño de estudio fue Cuantitativo, Descriptivo y Transversal, la población la constituyeron 100 adolescentes que acudieron al servicio de toco cirugía y gineceo obstetricia del Hospital General de Coyuca de Catalán, Guerrero. Con una Muestra de 30 adolescentes seleccionadas por medio del método probabilístico Muestreo Aleatorio Simple. Se aplicó cuestionario con categorías de respuesta dicotómicas y de opción múltiple para analizar la información se utilizó el programa SPSS Versión 15 empleando la correlación de Pearson para conocer el grado de asociación de las variables y Chicuadrada para probar la significancia de las diferentes proporciones. Resultados: El 50% de las adolescentes oscilan entre la edad de 18 a 19 años. Con un nivel escolar de preparatoria 43.3% el estado civil hallando una media entre las solteras y casadas. Se encontró correlación la edad del adolescente con el nivel escolar con una (r=.511, P=.004). También se encontró correlación con los métodos anticonceptivos con la religión con una (r=497, P=005) entre el método anticonceptivo elegido durante la estancia y la consejería que tiene con la enfermera es suficientes se encontró una correlación fuerte (r=.697 P=.000) en relación a las variables conocimiento que tienen las adolescentes de los métodos anticonceptivos y la enfermera realiza examen físico se encontró una correlación fuerte (r=.613, P=.000). Discusión: de acuerdo al hallazgo encontrado los métodos elegidos tienen que ver con la consejería que ofrece la enfermera estos resultados coinciden con los de Bernal, donde la consejería si influye en un 90%. Conclusión: La consejería que proporciona la enfermera es influyente en la decisión del método anticonceptivo.
Facultad de Enfermería. Maestría en Enfermería
Keywords: info:eu-repo/classification/cti/3; FE-M-2008-0006; Planificación familiar; Consejería; Adolescente; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5614